2009
DOI: 10.1177/0022034509346258
|View full text |Cite
|
Sign up to set email alerts
|

Mineralized Tissue Formation by BMP2-transfected Pulp Stem Cells

Abstract: Previously, in vitro differentiation of odontoblasts was shown for dental pulp stem cells (DPSCs) transfected with bone morphogenetic protein-2 (Bmp2). For this study, we hypothesized that such cells also show potential for mineralized tissue formation in vivo. DPSCs were transfected with Bmp2 and seeded onto a ceramic scaffold. These complexes were cultured in medium without dexamethasone, and thereafter placed subcutaneously in nude mice for 1, 4, and 12 weeks. Samples were evaluated by histology and real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 28 publications
(39 reference statements)
5
57
0
Order By: Relevance
“…An ectopic mouse model was used to evaluate the in vivo activity of ST Mi/GH 26,27) . Under isoflurane anesthesia, the backs of twelve 10-week-old BALB/c immunocompromised nude mice (SHIMIZU Laboratory Supplies, Kyoto, Japan) were washed, and disinfected.…”
Section: In Vivo Evaluation Of Odontoblastic Differentiation By St Mi/ghmentioning
confidence: 99%
“…An ectopic mouse model was used to evaluate the in vivo activity of ST Mi/GH 26,27) . Under isoflurane anesthesia, the backs of twelve 10-week-old BALB/c immunocompromised nude mice (SHIMIZU Laboratory Supplies, Kyoto, Japan) were washed, and disinfected.…”
Section: In Vivo Evaluation Of Odontoblastic Differentiation By St Mi/ghmentioning
confidence: 99%
“…DPSCs were placed into 96-well plates at a density of 2x10 4 cells per well and maintained overnight. The DPSCs were then treated with medicated media at various concentrations of the total flavonoid from Drynaria fortunei (0.01, 0.05 and 0.1 g/l) in a volume of 100 Âľl.…”
Section: Dpsc Proliferation Analysis Using Colorimetric 3-(4 5-dimetmentioning
confidence: 99%
“…Gronthos et al were the first to identify and isolate dental pulp stem cells (DPSCs) (2), and Grottkau et al demonstrated that DPSCs were undifferentiated mesenchymal stem cells in tooth pulp with self-renewal, regulated cell proliferation and the potential to transdifferentiate into various types of specialized tissue cells including osteoblast, adipocyte, neurocyte, chondrocyte and smooth muscle cells (3). Findings of recent studies suggested that DPSCs have the ability to differentiate into the bone cell phenotype in vitro and form mineralized tissue in vivo (4,5). These results suggest that DPSCs are likely have a positive impact on periodontal tissue engineering and bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…In the oral and maxillofacial area, there is a growing need to regenerate alveolar bone to treat periodontitis and for implant dentistry, and cell-based therapies are receiving increasing attention. 1,7,8,10,18,32 For dentists or oral surgeons, dental pulps and periodontal ligaments from discarded teeth, such as third molars, baby teeth that have fallen out, and premolars removed before orthodontic treatment are readily accessible and require an easy and minimally invasive procedure to obtain and store these tissues for future use. 9,11,21,23 Furthermore, banking a patient's own dental tissues is a reasonable and simple alternative to harvesting MSCs from other tissues.…”
Section: Discussionmentioning
confidence: 99%